2015
DOI: 10.3889/oamjms.2015.089
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Treatment of Pulmonary Valve Stenosis: A Single Center Experience

Abstract: BACKGROUND:Percutaneous pulmonary valvuloplasty is well established treatment of choice in pulmonary valve stenosis.AIM:The aim of our study was to present our experience with the interventional technique, its immediate and mid-term effectiveness as well as its complication rate.MATERIAL AND METHODS:The study included 43 patients, where 33 (74%) of them were children between the age of 1 month and 15 years.RESULTS:The procedure was successful in 38 patients or 90%. Mean peak to peak transvalvular gradient was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…A study from Iran 21 showed 57 % of patients had mild pulmonary regurgitation in the immediate post BPV period. Similarly, mild PR was noted in 55% of patients in Idrizi S et al study 22 while 34% patients developed mild PR in Qian X et al study. 14 The incidence of mild pulmonary valve regurgitation in immediate post BPV period was 48.8% in our study while there was not a single case of moderate or severe regurgitation.…”
Section: Discussionmentioning
confidence: 76%
“…A study from Iran 21 showed 57 % of patients had mild pulmonary regurgitation in the immediate post BPV period. Similarly, mild PR was noted in 55% of patients in Idrizi S et al study 22 while 34% patients developed mild PR in Qian X et al study. 14 The incidence of mild pulmonary valve regurgitation in immediate post BPV period was 48.8% in our study while there was not a single case of moderate or severe regurgitation.…”
Section: Discussionmentioning
confidence: 76%
“…PS may also be associated with a combination of infundibular hypertrophy and post stenotic dilation. These are frequently seen in older patients with longstanding PS and those with higher degree of valvular stenosis [11]. Post stenotic dilation and infundibular hypertrophy are more frequently seen in the nonreduced RVSP group or group 2 (47.2% and 62.9% respectively) but p value was not significant because of small sample size.…”
Section: Discussionmentioning
confidence: 82%
“…Розподіл пацієнтів в залежності від післяопераційних ускладнень наведено в таблиці 3. Таким чином наші дані співпадають з даними інших авторів [9]. У післяопераційному періоді помер 1 (1%) пацієнт внаслідок прогресуючої серцевої недостатності.…”
Section: Plys2005@ukrnetunclassified